2018
DOI: 10.1111/vsu.12968
|View full text |Cite
|
Sign up to set email alerts
|

Determination of surgical exposure obtained with integrated endoscopic thoracolumbar hemilaminectomy in large‐breed cadaveric dogs

Abstract: Objective: To define boundaries of minimally invasive integrated endoscopic hemilaminectomy at 4 sites in the canine thoracolumbar spine. Study design: Experimental, randomized cadaveric study. Animals: Six cadaver dogs that had been humanely euthanized for reasons unrelated to this study. Methods: Hemilaminectomy was performed with an integrated endoscopic system at T11-12, T12-13, L1-2, and L2-3, 1 at each site, on the left or right side of each dog. Each site was randomly assigned either a 19-mm or a 23-mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 17 publications
1
24
1
Order By: Relevance
“…We concluded that the minimally invasive intramuscular approach through a 2‐cm channel offered adequate access to the target area, with the tendinous attachment onto the articular process as the sole structure being cut. These findings support the reports of MISS cadaveric study on the feasibility of the techniques.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We concluded that the minimally invasive intramuscular approach through a 2‐cm channel offered adequate access to the target area, with the tendinous attachment onto the articular process as the sole structure being cut. These findings support the reports of MISS cadaveric study on the feasibility of the techniques.…”
Section: Discussionsupporting
confidence: 90%
“…Surgical loupes are popular among neurosurgeons but offer only limited magnification. The use of exoscopes and endoscopes has been reported in a few veterinary reports . Video‐assisted ventral slots have been used in cadavers and in clinically affected dogs, whereas mostly cadaveric studies have been reported for the thoracolumbar and lumbosacral region, with only one report of using an endoscope in a study in live dogs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In veterinary literature, most studies have evaluated a minimally invasive approach to the spine in canine cadavers or clinically normal dogs. For the thoracolumbar spine, endoscope-assisted [ 12 , 13 ] and full-endoscopic procedures have been reported [ 14 , 15 , 16 ]. A minimally invasive device with video assistance was used in studies with canine cadavers and in 10 clinical cases that underwent ventral slot decompression [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Standard approaches to the spine, so called open techniques , involve muscle dissection from the bony elements with removal of ligaments, tendons, and bony structures, which are all important parts of the dorsal stabilizing element of the spine . Because of the frequency of spinal surgery in dogs, interest in MISS has been growing . However, most studies are limited to dog cadavers; only two reports have described MISS thoracolumbar technique in live dogs .…”
Section: Introductionmentioning
confidence: 99%